Fighting Verses in the Holy Qur’an - An Interpretive Reading- - Ibrahim , Zaben (Islamic Sciences Journal, 2023)
The researcher dealt with the problem of suspicions about fighting verses, in which he clarified that Islam did not spread by the edge of the sword, and that the Holy Prophet - may Allah bless him and grant him peace - did not like blood in his character, nor did the people of Medina love wars. Studies have proven to Westerners that blood raises fear among Arabs, especially the Bedouins, and that fighting came to ward off danger and support the oppressed people and islam creed. The rule proved by the Holy Qur’an is that there is no compulsion in religion, and that the Noble Qur’an in all the verses of fighting did not say kill. On the contrary all the verses say fight those who fight you and this indicates the interaction, and urges the youth of the nation that Islam is the Islam of peace, affection and tenderness, and it is not permissible to oppose the infidels as long as they are peaceful. Indeed, the first verse of the Noble Qur’an, says that Allah is the Lord of the worlds and not only the Lord of Muslims. Key words: verses, fighting, the Qur’an, reading, exegesis